Brooke Bennett's Full Stroke at 215 m of Her 800 m Gold Medal Race at the Atlanta Olympic Games 1996 - Rushall, B. S.
Video pictures (25 frames) and the appropriate technical/ biomechanical explanations for Brooke Bennett's full stroke at 215 m of her 800 m gold medal race at the Atlanta Olympic Games 1996. Brooke Bennett's stroke makes a lot of sense from a propulsive perspective. It is almost continual and sacrifices overall length forward but not effective propulsive length. It is a stroke that supports a high rate for there is little wasted movement caused by any nnecessary actions or exaggerations. The subtle change in stroke length of the left arm between breathing and non-breathing strokes is caused possibly by the rotating head and some hyper-extension at the neck both "shortening" the ability of the musculature to facilitate extension forward. When the head is well down in the water and aligned in streamline with the torso the ability to reach forward is improved. That seems to be the most obvious reason for this small, but important, deviation in stroke. The tempo of this stroke is such that there is only time to comfortably perform a two-beat kick. To attempt more kicks would be excessively fatiguing as well as require a slowing of the arm cycles so that sufficient time would be available to complete the extra kicks. It is reasonable to assume that if Brooke Bennett attempted to alter her arm-stroking tempo or her kicking that her stroke movements would be altered considerably. Any such changes most likely would not be beneficial.